(untitled) (European Journal of Child Development, Education and Psychopathology, 2021)
The aim of this systematic review was to identify the evidence available in scientific literature in relation to moral development in educational contexts. The bibliographic databases of PubMed, Scopus, Psychology and Behavioral Science Collection (EBSCO) and Scielo were examined using predetermined search criteria and PRISMA methodology. Research studies published from 2010 to October 2020 were considered and, after evaluation, 3,021 articles dealing with the topic were identified and finally 167 articles were included in the review that met the inclusion criteria. The results suggest the influence of the educational context on moral development, from all levels of educational formation, where aspects, individual, cognitive, socioeconomic, intercultural, pedagogical, institutional, family and interactive converge, encouraging the development of studies that nourish the scientific discussion on the moral evolution of the human being and its associated training practices.